Processo de substituição de culturas de abastecimento alimentar pela cana-de-açúcar em Goiás (2003 a 2021) - Diniz, Amanda Silva (2023)
The substitution of food supply crops by sugarcane has become a controversial issue in many regions of Brazil and the world. One of these regions is Goiás, a state located in the centralwestern region of Brazil, which has had a significant increase in sugarcane production in recent decades. The hypothesis tested is that crops with greater expansion in the agroindustrial sector have a greater substitution effect in Goiás. Therefore, the aim of this study was to investigate the expansion of sugarcane cultivation in the state of Goiás and its potential impact on the substitution of other food crops. The study uses data from 2003 to 2021 on crop area, production, and prices of sugarcane, rice, beans, corn, and soybeans in the geographic mesoregions and microregions where production occurs. The data comes from various institutions, such as the Mauro Borges Institute, the Brazilian Institute of Geography and Statistics, the National Supply Company, the Union of the Alcohol Manufacturing Industry of the State of Goiás, and the Union of the Sugarcane Industry. The results demonstrated the dynamics of sugarcane expansion and its impact on the production of basic food crops such as rice and beans, as well as on expanding crops such as corn and soybeans. These results are important for the planning of agricultural production in the state and for informed decision-making regarding land use